Surface-induced synthesis and self-assembly of metal suprastructures - Li, Shaozhou (2012)
A systematic study on the synthesis of a series of self-assembled suprastructures, such as cubes, stars, belts, and microspheres, of Ag nanoparticles (AgNPs) in borosilicate glassware heavily cleaned with aqua regia is presented. These self-assembled structures are mostly formed from the crystallographically iso-oriented AgNPs, and exhibit well-defined shapes. In regular washed glassware, only Ag nanowires are synthesized. The formation mechanisms of these self-assembled Ag structures, based on monitoring of their structural evolution in glassware decorated with different molecules, are proposed. This work not only demonstrates that the surface energy of glassware can affect chemical synthesis, but also provides an interesting approach to the shape-controlled synthesis of novel self-assembled suprastructures of AgNPs, which could be potentially used as synthesis templates, drug vessels, and microreactors.